EDUKASI KETERAMPILAN SOFT SKILLS ENTREPRENEURSHIP - Simarmata, Jonner (JUBDIMAS ( Jurnal Pengabdian Masyarakat), 2024)
The Community Service Program entitled "Implementation of the Cultivation of Awareness of the Importance of Soft Skills Entrepreneurship Skills Through the Development of Universitas Batanghari Jambi Students" aims to provide experience for students to care about the development of cooperatives. Schools are expected to be a means for students to learn to run small businesses, develop organizational skills, encourage habits to innovate, learn to solve problems and as a place for students to face the world of work after graduating from school. This Community Service Program will be carried out on Universitas Batanghari Jambi Students. School cooperatives can provide experience for students to care about the development of cooperatives. School cooperatives are expected to be a means for students to learn to run small businesses, develop organizational skills, encourage habits to innovate, learn to solve problems and so on.